2022
DOI: 10.1107/s1600577522004489
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Langendorff system of the isolated beating heart for experimental radiotherapy at a synchrotron: 4000 Gy in a heart beat

Abstract: Microbeam radiotherapy could help to cure malignant tumours which are currently still considered therapy-resistant. With an irradiation target in the thoracic cavity, the heart would be one of the most important organs at risk. To assess the acute adverse effects of microbeam irradiation in the heart, a powerful ex vivo tool was created by combining the Langendorff model of the isolated beating mammalian heart with X-Tream dosimetry. In a first pilot experiment conducted at the Biomedical and Imaging Beamline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…No significant changes regarding baseline tone and maximal contraction force were determined, but the peak latency was found to be increased, and in addition, the maximal force change decreased after MBI. These results align with the findings in cardiac physiological studies [33,34] during and after MBI. In these studies, rodent hearts in the Langendorff perfusion system were irradiated with MBI peak doses up to 400 Gy and 4000 Gy, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No significant changes regarding baseline tone and maximal contraction force were determined, but the peak latency was found to be increased, and in addition, the maximal force change decreased after MBI. These results align with the findings in cardiac physiological studies [33,34] during and after MBI. In these studies, rodent hearts in the Langendorff perfusion system were irradiated with MBI peak doses up to 400 Gy and 4000 Gy, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…While the initial focus of MBI development was in the brain, more recent studies have also shown good normal tissue tolerance in the lung [31] and efficiency in treating lung tumors in a small animal model [32]. In an ex vivo study, it was shown that, even with peak doses up to 400 Gy, MBI could be conducted without severe acute effects on cardiac function [33,34]. In addition to the heart, the esophagus is also an organ at risk (OAR) in thoracic irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the experimental model developed by Langendorff and his predecessors has undergone many modifications and alterations, the basic principles and ideas remain relevant in contemporary research. Currently, isolated heart models are extensively used for pharmacological testing, allowing researchers to directly observe the effects of drugs on heart rate, rhythm, contractility, and metabolic pathways without the confounding variables present in whole-animal studies [47][48][49]. They are also crucial in disease modeling, simulating conditions such as ischemia-reperfusion injury, hypertrophy, and heart failure to understand underlying mechanisms and test therapeutic interventions.…”
Section: Current Uses and Future Perspectives Of Isolated Heart Perfu...mentioning
confidence: 99%
“…Researchers from China Pharmaceutical University [8] have optimized and improved the perfusion and culture device in recent years, which can achieve perfusion and culture of mammalian cells in suspension, providing a reference for three-dimensional cell culture technology. Langendorff perfusion method, a famous isolated heart perfusion technology [9] . With the development of cardiovascular research in recent years, this experimental instrument and technology have also made many improvements.…”
Section: Introductionmentioning
confidence: 99%